Pulmonary embolism in a 51-year-old woman with chronic kidney disease - Indra Dewi, Triwedya; Hasan, Melawati; Fathini, Fathy (Universa Medicina, 2021)
Background Chronic kidney disease (CKD) is a worldwide public health problem both in terms of the number of patients and the cost of treatment. Chronic kidney disease seems to be the main driver of pulmonary embolism (PE) in dialysis patients. The diagnosis of PE is difficult due to its non-specific signs and symptoms, especially in many comorbidities with similar features. Chronic kidney disease plays a role in both the incidence of venous thromboembolism and the manifestations of pulmonary hypertension, resulting in an increased risk of morbidity and mortality. Advances in the management of patients with suspected PE have improved diagnostic accuracy. An approach using several diagnostic tools with different characteristics, such as D-dimer measurement, and imaging tests-predominantly computed tomography pulmonary angiography (CTPA) - can help evaluate the diagnosis. Case DescriptionHere we report the case of a 51-year-old woman with a history of chronic kidney disease, who presented with sudden worsening of dyspnea. Further examination showed signs of right heart failure with a high probability of pulmonary hypertension on echocardiography. Based on the general features it is difficult to distinguish between acute pulmonary embolism and chronic pulmonary hypertension, both of which can be caused by the underlying chronic kidney disease. Nevertheless, gold standard imaging using CTPA confirmed the diagnosis of pulmonary embolism, with underlying pulmonary hypertension from chronic kidney disease. ConclusionsThe diagnosis of pulmonary embolism with comorbidities is challenging. The availability of diagnostic modalities will confer different advantages and particular accuracy to meet the challenges in diagnosis.